2003
DOI: 10.1046/j.1365-313x.2003.01726.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a tomato protein that inhibits a xyloglucan‐specific endoglucanase

Abstract: SummaryA basic, 51 kDa protein was puri®ed from suspension-cultured tomato and shown to inhibit the hydrolytic activity of a xyloglucan-speci®c endoglucanase (XEG) from the fungus Aspergillus aculeatus. The tomato (Lycopersicon esculentum) protein, termed XEG inhibitor protein (XEGIP), inhibits XEG activity by forming a 1 : 1 protein:protein complex with a K i % 0.5 nM. To our knowledge, XEGIP is the ®rst reported proteinaceous inhibitor of any endo-b-1,4-glucanase, including the cellulases. The cDNA encoding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 75 publications
4
71
0
2
Order By: Relevance
“…In a superimposition of the structure of a catalytically inactive Bacillus circulans xylanase mutant complexed with xylobiose (PDB code 1bcx) (36) (in subsites Ϫ1 and Ϫ2) with the structure of the ANXI⅐TAXI-I complex (root mean square deviation of 0.6 Å for 181 xylanase C␣ atoms), five Leu 292 atoms (N, C ␣ , C ␤ , C ␥ , and C ␦1 ) coincide with C-5, O-5, C-1, C-2 and O-2 of the xylose in subsite Ϫ2 (Fig. 3B) TAXI-I displays significant sequence similarity with a carrot extracellular dermal glycoprotein (37), a tomato xyloglucanspecific endoglucanase inhibitor protein (38) and with TAXIlike proteins (16) identified in barley (HVXI), rye (SCXI-I to SCXI-IV), and durum wheat (TDXI-I and TDXI-II). In addition, screening of the available data bases revealed that multiple TAXI-I homologous genes also occur in soybean, rice, and Arabidopsis thaliana (16).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a superimposition of the structure of a catalytically inactive Bacillus circulans xylanase mutant complexed with xylobiose (PDB code 1bcx) (36) (in subsites Ϫ1 and Ϫ2) with the structure of the ANXI⅐TAXI-I complex (root mean square deviation of 0.6 Å for 181 xylanase C␣ atoms), five Leu 292 atoms (N, C ␣ , C ␤ , C ␥ , and C ␦1 ) coincide with C-5, O-5, C-1, C-2 and O-2 of the xylose in subsite Ϫ2 (Fig. 3B) TAXI-I displays significant sequence similarity with a carrot extracellular dermal glycoprotein (37), a tomato xyloglucanspecific endoglucanase inhibitor protein (38) and with TAXIlike proteins (16) identified in barley (HVXI), rye (SCXI-I to SCXI-IV), and durum wheat (TDXI-I and TDXI-II). In addition, screening of the available data bases revealed that multiple TAXI-I homologous genes also occur in soybean, rice, and Arabidopsis thaliana (16).…”
Section: Resultsmentioning
confidence: 99%
“…Based on a rapid increase of the carrot extracellular dermal glycoprotein mRNA level in response to wounding, it was suggested to be a plant defense protein (37). Recent characterization of tomato xyloglucan-specific endoglucanase inhibitor protein revealed a possible plant defense function as an inhibitor of a microbial glucanase of GH family 12 (38). Moreover, GH family 12 glucanases share a common ␤-sandwich fold with GH family 11 xylanases.…”
Section: Resultsmentioning
confidence: 99%
“…Plant β-Dxylosidases have been suggested to be involved in cell-wall remodeling (Goujon et al, 2003). Surprisingly, the 51 kDa band that was more abundant in silenced cellsuspension culture medium was identified by the MSMS of 4 peptides as the xyloglucan-specific endoglucanase inhibitor protein XEGIP (total MASCOT score 113; accession number AY155579; Qin et al, 2003). This protein has been shown to form a complex with the xyloglucan-specific endoglucanase from Aspergillus aculeatus, inhibiting its glucanase activity.…”
Section: Anomalous Protein Secretion In Culture Medium Of Lepldβ1-silmentioning
confidence: 99%
“…71 Depolymerization of xyloglucan has been proposed to play an important role during both cell wall expansion and pathogen invasion. [72][73][74] Endo-β-1,4-xylanases are key enzymes in the degradation of xylans and a number of endoxylanases are produced by microbial pathogens to break through the plant cell wall. Rice plants expressing a thermostable exogenous xylanase gene (ATX) exhibited upregulation of SOD, CAT and xylanase inhibitor (RIXI) genes, which could play roles in plant defense.…”
Section: Post-synthetic Modifications Of the Cell Wall Affect Cwi Andmentioning
confidence: 99%